Regional Innovation – A Pillar of Regional Competitiveness and an Object of Regional Development Policy - RĂDOI, Mihai Ionuț; ȘERBAN, Răzvan (Journal of Advanced Research in Management; Vol 10 No 1 (2019): JARM Volume X Issue 1(19) Summer 2019, 2019)
The developed economy of the future can be predicted with enough accuracy as a global economy. A democratic and efficient policy is without any doubt regional and local. Taking into account the fact that the economic growth in EU does not exceed the average of 2,4% (calculated from the real GDP) under normal economic circumstances and taking into account that the United States reached the current average level of GDP/capita in EU from 1985 we can say that in this moment EU needs a distinct competitive pattern in order to ”overcome the stages”. In order to achieve this, Europe needs to adapt to the tactical growth factors nowadays – to the technological innovation and the cost reduction of the main competitors, to the achievement of the desideratum of the Union, which are growing and developing according to a completely new paradigm, with a regional horizon, thus representing an innovative approach. On the other hand, the contemporary development entered in the last years under the auspices of sustainability. Even since the adoption of the United Nations Brundtland Report from 1987, the coordinates of the economic activity were shed in a new light. The constraints of the economic growth in harmony with a renewable environment, turned this problem into a ”countervailing” one that is between prosperity and sustainability. Nowadays, this vision is no longer acceptable for at least three reasons. Globalization, climate changes and the reduction of the development disparities, respectively the living standard for a significant part of the planet lead inevitably to new clustered development paradigms.